An Analysis of Selective Student Participation in English as a Foreign Language Learning: A Qualitative Study on the Stage-Dependent Efficacy of Think-Pair-Share - Nurul Aini Savitri; Loli Safitri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study explores student participation (SP) paradoxes during the Think-Pair-Share (TPS) process in an eleventh-grade EFL setting. Despite TPS's reputation for engagement, observations at SMA N 1 Talang Kelapa revealed inconsistent participation levels. Using a descriptive qualitative design, student involvement was tracked across seven indicators. Findings indicate that participation is phase-dependent: the Pairing phase saw robust, universal engagement, whereas the Thinking phase was marked by cognitive passivity. The Sharing phase highlighted significant socio-affective barriers, with students relying on teacher intervention or peer copying due to performance anxiety. These results suggest that while TPS excels in collaborative rehearsal, it falters during stages requiring individual accountability and higher-order thinking.